VIRTUAL SELECTIVITY PEPTIDES OF CSN1S2 PROTEIN OF LOCAL GOAT ETHAWAH BREEDS MILK MODULATE BIOLOGICAL MECHANISM OF CALMODULIN - FATCHIYAH FATCHIYAH,; SENTOT J RAHARJO,; FIRLI RP DEWI, (International Journal of Pharma and Bio Sciences, 2015)
The purpose of our study is to observe virtual selectivity peptides of caprine alpha-S2 casein (CSN1S2) protein of goat Ethawah breeds milk modulate biological mechanism of Calmodulin virtual prediction of biological function of peptides of goat fresh milk of local Ethawah breed. The caprine alpha-S2 casein protein was isolated and purified from fresh goat milk local Malang, and then caprine alpha-S2 casein protein was sequenced by MALDI-TOFF analysis. The function of specific peptides were docking with Calmodulin by in silico.The result of this study is the caprine alpha-S2 casein protein of Ethawah breed goat milk has eight peptide fragments: CSN1S2 f41-47, f87-96, f97-107, f131-141, f182-189, f205-213, 214-221 and f214-223. The most of alpha-S2 casein peptide fragment can interacted properly with Calmodulin, except CSN1S2 fragment 97-107 peptide. The caprine alpha-S2 casein protein peptides have ability to bind Calmodulin on specific site and may enhance sites for interactions with other cellular molecules.